FINANCIAL EDUCATION, FINANCIAL STRESS, AND FINANCIAL WELL-BEING: THE STRATEGIC ROLE OF FINANCIAL TECHNOLOGY FOR MILLENNIAL BANK EMPLOYEES IN NORTH SUMATRA - Roni Parlindugan Sipahutar; Dedeng Irawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of financial education and financial stress on financial well-being, with financial technology considered as a mediating variable. The research is driven by the increasing role of financial literacy and digital financial services in helping individuals manage financial challenges in today’s digital era. A quantitative approach with a deductive design was employed, using structured questionnaires distributed to 400 millennial respondents aged 25–40 years working in the banking sector in North Sumatra. Data were analyzed with Partial Least Square–Structural Equation Modeling (PLS-SEM), which enables simultaneous testing of measurement and structural models. The results indicate that financial education has a positive and significant effect on both financial technology adoption and financial well-being. In contrast, financial stress is negatively associated with financial well-being but positively influences the adoption of financial technology as an adaptive mechanism to cope with financial pressures. Furthermore, financial technology is found to play a crucial mediating role, strengthening the effects of financial education and mitigating the negative impact of financial stress on financial well-being. The study provides theoretical contributions by extending the existing frameworks that link financial literacy, stress, technology, and financial outcomes. From a practical perspective, the findings highlight the importance of promoting digital-based financial education programs and developing inclusive financial technology solutions to enhance financial well-being, particularly among younger generations in the banking industry